Readiness of Slovenian Students for Age and Cultural Diversity in the Workplace: Analysis of Attitudes toward Older Migrants - Uliueva, Anna; Dežman, Marina (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
In the context of demographic crisis and increasing net migration, the involvement of older migrants in active labour activity is an important task for emerging “longevity society.” The study presented in this article is aimed at identifying latent contradictions in the attitudes of Slovenian students toward cooperating with older migrants, as future recruitment specialists, managers and employees working in multicultural teams. The results obtained demonstrate that students’ attitudes toward older migrants in the workplace do not represent coherent attitudinal constructs ranging from negative to positive, but rather a space of semantic tension in which declared norms of inclusivity conflict with persistent stereotypes about them. The study contributes to the discussion on managing age and cultural diversity under conditions of demographic change and proposes a non-standard methodological tool for the in-depth analysis of latent social attitudes.